Hepatic arterial infusion chemotherapy for colorectal liver metastases revisited. Issue 9 (September 2020) - Chouliaras, Konstantinos; Russell, Greg; Levine, Edward; Howerton, Russell; Votanopoulos, Konstantinos; Clark, Clancy; Shen, Perry
Abstract: Background: Recent reports indicate improved survival in patients undergoing surgical treatment for colorectal liver metastases (CRLM) with hepatic arterial infusion (HAI) pump chemotherapy compared to surgery alone. Methods: Patients who underwent resection and/or ablation of CRLM between 1996 and 2016 were included from a single-institution prospectively maintained database. Proportional hazards regression analysis was performed to determine predictors of overall survival (OS) and 3:1 propensity score analysis (PSA). Results: Of 349 patients included, 36 had HAI pumps placed (HAI group) and 313 did not (no-HAI group). There was no difference in primary tumor grade (p = 0.24), ECOG status (p = 0.44), tumor number (p = 0.1), tumor size (p = 0.56), margin status (p = 0.76) between the two groups. Median overall survival was 44.7months vs 37.1months for the HAI versus no-HAI group (p = 0.01). Cox proportional hazards regression analysis demonstrated positive margin status (HR:2.47, p < 0.0001), HAI therapy (HR:0.56, p = 0.02), preoperative chemotherapy (HR:0.69, p = 0.02) and tumor diameter (HR:1.07, p = 0.005) as predictors of OS. In 3:1 PSA, 32 HAI subjects were matched with 87 non-HAI subjects balancing all covariates. Median OS was 42.4 months versus 35.6 months for the HAI versus no-HAI group (p = 0.03). Conclusion: Surgical treatment of CRLM combined with HAI chemotherapy is associated with improved OS compared to surgery alone. Further study of this treatment approach is indicated.